Super-High-Frequency Bulk Acoustic Resonators Based on Aluminum Scandium Nitride for Wideband Applications - Wentong Dou; Congquan Zhou; Ruidong Qin; Yumeng Yang; Huihui Guo; Zhiqiang Mu; Wenjie Yu (Nanomaterials, 2023)
Despite the dominance of bulk acoustic wave (BAW) filters in the high-frequency market due to their superior performance and compatible integration process, the advent of the 5G era brings up new challenges to meet the ever-growing demands on high-frequency and large bandwidth. Al1-xScxN piezoelectric films with high Sc concentration are particularly desirable to achieve an increased electromechanical coupling (Kt2) for BAW resonators and also a larger bandwidth for filters. In this paper, we designed and fabricated the Al1-xScxN-based BAW resonators with Sc concentrations as high as 30%. The symmetry of the resonance region, border frame structure and thickness ratio of the piezoelectric stack are thoroughly examined for lateral modes suppression and resonant performance optimization. Benefiting from the 30% Sc doping, the fabricated BAW resonators demonstrate a large effective electromechanical coupling (Keff2) of 17.8% at 4.75 GHz parallel resonant frequency. Moreover, the temperature coefficient of frequency (TCF) of the device is obtained as −22.9 ppm/°C, indicating reasonable temperature stability. Our results show that BAW resonators based on highly doped Al1-xScxN piezoelectric film have great potential for high-frequency and large bandwidth applications.